Movement velocity as an indicator of mechanical fatigue and resistance exercise intensity in cross modalities - de-Oliveira, L. A.; Aragão-Santos, J. C.; Heredia-Elvar, J. R.; Da Silva-Grigoletto, M. E. (Research Quarterly for Exercise and Sport, 2023)
Purpose: This study analyzed the acute mechanical response to three workouts of the day (WOD) protocols in as many repetitions as possible (AMRAP), every minute on the minute (EMOM), and for time (FT) models by quantifying the degree of mechanical fatigue induced by popular resistance exercises in the Cross modalities, front squat (FS), and shoulder press (SP). We also analyzed whether the exercises` fastest velocity (Vfastest) could be an objective indicator of relative intensity (%1RM).